Determining the level of development of the young sportswomen flexibility in sports aerobics - Мошенська Тетяна Валеріївна, (Tetiana Moshenska); Бодренкова Інна Олексіївна, (Bodrenkova Inna) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: To develop and prove experimentally methodology development athletes flexibility in initial specialization in sports aerobics. Material and methods: we used pedagogical research methods and methods of mathematical statistics. Results: the basic tools, methods, techniques, and requirements for the exercises, which were the contents of the experimental method development flexibility that will improve the quality of competitive elements and combinations in sports aerobics. Conclusions: the use of the author’s methodology development flexibility in sports aerobics provide a higher growth rate of the studied parameters.